2016
DOI: 10.1136/bjophthalmol-2016-309490
|View full text |Cite
|
Sign up to set email alerts
|

Intake of key micronutrients and food groups in patients with late-stage age-related macular degeneration compared with age–sex-matched controls

Abstract: This study showed significant differences in intakes of vitamins C and E, beta-carotene, folate and vegetables between patients with late-stage AMD and healthy controls, and thus has provided a better understanding of the nutritional intake of patients presenting with advanced AMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 30 publications
1
16
1
1
Order By: Relevance
“…Unlike in other studies [ 8 , 16 ], no statistically significant associations were observed in nonsmokers and AMD. We found inverse associations between F&V and AMD in current smokers only.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Unlike in other studies [ 8 , 16 ], no statistically significant associations were observed in nonsmokers and AMD. We found inverse associations between F&V and AMD in current smokers only.…”
Section: Discussioncontrasting
confidence: 99%
“…We found inverse associations between F&V and AMD in current smokers only. Several studies reported that high fruit and vegetable intake is inversely associated with AMD [ 8 , 16 ]. A cross-sectional study conducted in Australia showed that the proportion of individuals who met the recommended daily intake of vegetables was lower amongst patients with late-stage AMD than in a population of age- and sex-matched controls with no signs of AMD (52.9% vs. 64.5%, p = 0.0002) [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data from the FFQ were coded into a customized database that incorporated the nutrient tables for use in Australia (NUTTAB 2010) . Nutrient associations for energy‐adjusted intake were between 0.50 and 0.60, similar to other studies . Foods were categorized into major food categories and sub‐categories to determine servings per day.…”
Section: Methodssupporting
confidence: 75%